1994
DOI: 10.1207/s15326888chc2301_1
|View full text |Cite
|
Sign up to set email alerts
|

How Parents Cope With the Experience of Neonatal Intensive Care

Abstract: Thirty-two mothers and 25 fathers described their coping efforts during the initial weeks of their preterm infants' hospitalization in a neonatal intensive care unit. Utilizing procedures developed by Lazarus and Folkman (1984) in which coping is linked with a specific stressful event, parents reported what they did to cope with the stressor they perceived to be the most stressful. They also completed the Ways of Coping Questionnaire (Folkman & Lazarus, 1988). Results showed that there were similarities and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 9 publications
4
51
1
1
Order By: Relevance
“…78.3% of this support came from those around mothers, while 51.7% came from health care workers. The next most-common strategies were solving problems gradually by planning for the LBW infant's care (55%) and making a care plan for when the infant came home (53.3%) ( This confirms the results of Hughes, McCollum, Sheftel, & Sanchez, (1994) study with the same population, where the largest proportion of maternal coping was accounted for by Seeking Social Support (24%). Also Seideman et al, (1997) study showed that the parents were found to have coped by using a problem-focused approach by seeking information about their infants' progress from the medical and nursing staff When we examined deep coping strategies that focus on emotional adjustment, the most common approach was finding positive meaning through prayer (86.7%).…”
Section: Fig 1: Maternal Stress Level On Lbw Birthsupporting
confidence: 73%
“…78.3% of this support came from those around mothers, while 51.7% came from health care workers. The next most-common strategies were solving problems gradually by planning for the LBW infant's care (55%) and making a care plan for when the infant came home (53.3%) ( This confirms the results of Hughes, McCollum, Sheftel, & Sanchez, (1994) study with the same population, where the largest proportion of maternal coping was accounted for by Seeking Social Support (24%). Also Seideman et al, (1997) study showed that the parents were found to have coped by using a problem-focused approach by seeking information about their infants' progress from the medical and nursing staff When we examined deep coping strategies that focus on emotional adjustment, the most common approach was finding positive meaning through prayer (86.7%).…”
Section: Fig 1: Maternal Stress Level On Lbw Birthsupporting
confidence: 73%
“…Many studies (2,(31)(32)(33) show that mothers experience frustration when separated from their newborn infant. When separation occurs, mothers and their infants have no opportunity to experience mutual bonding and recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that mothers felt positive support from the staff. According to previous research (29,31), that sense of support is important in order for parents to handle the situation of having a preterm infant who needs care in a neonatal unit. When the infant's condition is stabilized, parents of a preterm infant have more time and psychological space for their own emotions.…”
Section: Discussionmentioning
confidence: 99%
“…According to them, fathers experience, among others, 'immense anxiety', 'helplessness', 'fear of the unknown', and 'constraints with work' during the hospitalisation period of their child. Fathers tend to look for a 'planful problem-solving' coping strategy in the NICU (Hughes et al, 1994;Affleck et al, 1991). Furthermore, fathers experience difficulty in choosing between time spent with their child and at work (Premberg et al, 2011;Pohlman, 2005) and they tend to see their spouse's and child's needs as a higher priority than their own (Pohlman et al, 2007).…”
Section: Design Of 'For Daddy'mentioning
confidence: 99%